Navigating Liminal Spaces in University-Community Engagement: Risky Collaboration in Times of Crisis - Lisa Porter; Daniel Beers; Joseph LeBlanc; Diana Meza; Ekaterina Koubek (The University of Alabama, 2023)
When the COVID-19 pandemic forced P-12 schools to temporarily transition to online learning, it exacerbated the already deep-seated educational inequities in communities across the United States. Employing a grounded theory approach, this paper explores how educators and community stakeholders created a free full-time volunteer-led K-2 learning pod for historically underserved students. The authors discuss the opportunities and challenges experienced in the pod's implementation, as well as lessons for these types of university-community partnerships. The findings of the study reveal the potential of equity-focused collaborations that accept risk, occupy uncomfortable liminal spaces, and leverage informal networks and relationships to build trusting and authentic community partnerships. The paper concludes with a call to reimagine the parameters of university-community engagement in times of crisis.